Optical Routers Based On Microring Resonator For Optical Networks-On-Chip - Hazura, Haroon; Nadia, A. A.; Hanim, Abdul Razak; Anis Suhaila, Mohd Zain; S. K., Othman; Fauziyah, Salehuddin (Penerbit Universiti, UTeM, 2016)
Optical technology has boosted the revolution of Optical Networks-on-Chip (ONoC). In this paper, a passive microring resonator (MRR) semiconductor switching element is proposed. The design of a resonator router based on high-order of microring resonators is demonstrated in Silicon-on-Insulator (SOI). The suitability of the MRR as the basic building block for ONoC applications was investigated based on the insertion loss, extinction ratio (ER) and FSR. This model was designed on the silicon and modeled using COMSOL software. The result shows that excellent performance was achieved with huge FSR, low insertion loss, 3-dB bandwidth of less than 2nm and high extinction ratio.